2015
DOI: 10.1111/jlme.12292
|View full text |Cite
|
Sign up to set email alerts
|

Return of Genetic Research Results to Participants and Families: IRB Perspectives and Roles

Abstract: Whether or not to offer individual genetic results to research participants has been the subject of considerable debate, yet consensus regarding what, when, and how to return remains elusive. Despite this lack of clarity, the discussion has moved to the offer of research results to family members of participants, including when the participant is deceased. Given the familial implications of genetic information, this extension is perhaps logical. But it raises concerns throughout the research process, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Generally, members of IRBs thought that research findings should be returned, provided participants want to know their results [ 44 , 150 ]. However, while in one study 15/22 (68%) agreed that participants should ‘probably’ or ‘definitely’ be offered the choice to receive results that may be useful for participants’ or family’s health [ 151 ], another study indicated that a large majority of the 65 Chairs of US IRBs studied favoured offering the result to participants, even if there is a lack of clear utility associated with the findings [ 149 ]. One study explored views of a cohort of Canadian IRB members, coordinators, and chairs on returning IRR [ 152 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, members of IRBs thought that research findings should be returned, provided participants want to know their results [ 44 , 150 ]. However, while in one study 15/22 (68%) agreed that participants should ‘probably’ or ‘definitely’ be offered the choice to receive results that may be useful for participants’ or family’s health [ 151 ], another study indicated that a large majority of the 65 Chairs of US IRBs studied favoured offering the result to participants, even if there is a lack of clear utility associated with the findings [ 149 ]. One study explored views of a cohort of Canadian IRB members, coordinators, and chairs on returning IRR [ 152 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Five studies, all from North America, explored views of IRBs on the return of SSR [44,[149][150][151][152]. Generally, members of IRBs thought that research findings should be returned, provided participants want to know their results [44,150].…”
Section: Clinical Research Settingmentioning
confidence: 99%
“…Engagement of underrepresented populations in genomic research has been studied in various settings [12][13][14]. Several studies have examined how to return results to various demographic groups, including minors, adults who lack decision-making capacity, and relatives of deceased persons [15][16][17][18][19][20]. Very few studies have examined RoR in low-resource clinical environments such as federally qualified health centers [21].…”
Section: Introductionmentioning
confidence: 99%
“…The preferences of research participants with regards to receiving their personal or their child’s genetic results vary, where many are interested while some are not [ 9 ]. Researchers may have the responsibility to return genetic results to participants, when these lead to changes in the participants’ healthcare [ 10 ]. There are several recommendations on the ethical obligations of researchers for RoR in the research context [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%